Assignation of transit fluxes in a next of urban transport - Canales García, Pedro (2003)
The assignation of traffic flow to an urban transportation network can be done using Wardrop's equilibrium principle, which deals the election of travel routes by the users. This election is done under the hypothesis of uniform information to users based on the perception they have of a minimum travel costs between the travel origin-destination. According to this principle, in the network flow point, none of the users would improve their travel costs changing the route initially chosen unilaterally. The traffic flow in these conditions are called user's deterministic traffic flow. In this work, we consider interest of the network administrator in optimizing his investment as well as the interest of the users to minimize travel costs. In this case, it's necessary to formulate a model which picks both interest. This gave rise to a mathematical formulation in two levels. The second level on this model describe the user problem by mathns of variational inequality. This formulation is known as a generalized two-level programm.